Analysis of accuracy and time for the two-in-one navigation registration technique in dynamic navigation implantation: an in vitro study - XU Min; WEI Shimin; SHI Junyu; LAI Hongchang (Shanghai Jiaotong Daxue xuebao. Yixue ban)
Objective·To assess the accuracy and time of the two-in-one registration technique by comparing it with the U-shaped tube registration in dynamic navigation implantation.Methods·Thirty standardized 3D-printed models with mandibular posterior sites missing a single tooth were randomly divided into three groups: two-in-one registration group, U-shaped tube registration group and free-hand implantation group, and the implant surgical plan was designed by the “YIZHIMEI” DCARER oral implant surgery navigation system. Cone beam CT before and after operation was taken. The implant platform deviation, implant apex deviation and angular deviation of the actual implant positions and the designed implant positions were measured. The operating time for using two-in-one registration technique and the U-shaped tube registration technique was recorded to evaluate the complexity of the two registration techniques. The one-way ANOVA and SNK (Student-Newman-Keuls) test were used to analyze the implant platform deviation, implant apex deviation and angular deviation of each group.Results·There were no statistically significant differences in implant platform deviation, implant apex deviation and angular deviation between the two-in-one registration group and the U-shaped tube registration group (P>0.05). However, the implant platform deviation, implant apex deviation and angular deviation of the two-in-one registration group and the U-shaped tube group were lower than those in the free-hand implantation group, and the differences were statistically significant (P<0.001). The operating time required for the two-in-one registration was shorter than that for the U-shaped tube registration process, and the difference was statistically significant (P<0.001).Conclusion·The accuracy of the two-in-one dynamic navigation registration technique used in implanting on a model of mandibular posterior sites missing a single tooth is similar to that of the U-shaped tube dynamic navigation registration technique. But the two-in-one registration takes less time for registration procedure than the U-shaped tube registration, and is easier to operate.